Bauteilfinishing durch CO2-Trockeneisstrahlen - Automatisierbare Nachbearbeitungsprozesse durch innovative Fertigungstechnologien - Amon, Sven; Gross, Daniel; Hanenkamp, Nico (wt Werkstattstechnik - Online, 2019)
Zur Produktivitätssteigerung ist eine ganzheitliche Optimierung von Prozessketten erforderlich. Auch innovative Fertigungstechnologien wie die additive Fertigung fordern ressourcenintensive und nicht-wertschöpfende Nachbearbeitungsprozesse. Das Entfernen von verfahrensbedingten Fertigungsrückständen sowie Materialanhaftun-gen wie Stützstrukturen ähnelt der Gratbeseitigung subtraktiver Fertigung. Für beide Herausforderungen bieten CO2-basierte Strahl-verfahren einen effizienten Lösungsansat
Keywords: Fertigungstechnik; Additive Fertigung; Automatisierung

Erweitertes Prozessverständnis erleichtert das Bauteilfinishing - Amon, Sven; Pour Abdollahyan, Fardin; Gross, Daniel; Hanenkamp, Nico (Werkstatt und Betrieb, 2019)
Das Finishing steht durch vorwiegend manuelle Bearbeitungskonzepte im Widerspruch der Automatisierungstrends. Neue Erkenntnisse zum Finishen mit Trockeneis ermöglichen Anwendern Ansätze für leicht zu automatisierende Technologien bereits im Vorfel
Keywords: Entgraten; Abtragen von Stützstrukturen; Reinigung; Finishing; Automatisierung

Gratentfernung durch Trockeneis - Amon, Sven; Viner, Alexander; Hanenkamp, Nico (JOT, Journal fuer Oberflaechentechnik, 2022)
Die Entgratung stellt insbesondere bei schwer zugänglichen Graten eine Herausforderung dar. Trockeneisstrahlen kann durch die Verwendung von recyceltem CO2 einen sauberen, nachhaltigen und wirtschaftlichen Lösungsansatz bieten. Erste Ergebnisse einer laufenden Studie zeigen eine zuverlässige Gratentfernung bei verschiedenen metallischen Werkstoffen.<br
Keywords: Entgratung; Trockeneisstrahlen; Finishing; Endbearbeitung

Hybrid Supply System for Conventional and CO2/MQL-based Cryogenic Cooling - Hanenkamp, Nico; Gross, Daniel; Amon, Sven (Procedia CIRP, 2018)
Increasing demand for difficult-to-cut materials challenge conventional cooling techniques to their limit. The durability of the tool is often reduced and cutting parameters such as feed rate or depth of cut have to be adjusted with a negative impact on productivity. Therefore, innovative cooling technologies have to be developed and integrated into new and existing machining equipment. The article describes the development of a hybrid cooling concept offering the flexibility to assign conventional or cryogenic cooling to incremental process steps. The developed cryogenic cooling supply system controls the flow of liquid carbon dioxide regarding density, flow rate and temperature before the lubrication media is injected by a high precision pump into the same tube. This approach significantly reduces the integration effort especially for internal cooling before being applied to a drilling process with a rotating tool of 50CrMo4. The challenges for the integration in the machine tool consist in the interface between spindle and tool holder and the tool itself due to the potential expansion of CO2 leading to undesired cooling before reaching the tool center point. Therefore, each interface has been investigated and requirements for cryogenic-compatible tools have been defined. Finally, different lubrication fluids combined with CO2-based cryogenic cooling have been investigated regarding tool durability for a milling process of Ti6Al4V. The results show that different oils have significant impact on the process performance offering a perspective for further research.<br
Keywords: Cryogenic Cooling; Minimum Quantity Lubrication

Influence of dry ice blasting process properties on surface roughness and residual stresses of machined and additive manufactured workpieces - Amon, Sven; Jobst, Andreas; Merklein, Marion; Hanenkamp, Nico (Procedia CIRP, 2022)
Dry ice blasting has shown the potential to remove metallic burrs after machining processes and support structures after additive manufacturing. During blasting, process parameters need to be chosen depending on the material and the geometric properties of the burr. However, dry ice blasting affects the local material properties on a micro level and improper blasting parameters may lead to changes in the part surface. In this article, correlations and interactions between dry ice blasting parameters and resulting specimen roughness and residual stresses are identified for machined and additive manufactured metallic materials.<br
Keywords: dry ice blasting; metallic edge zone; deburring; post-processing; residual stresses

Investigation of Carbon Dioxide Based Blasting Technologies as Cryogenic Deburring Method for Titanium Alloy and Stainless Steel - Gross, Daniel; Heinz, Andrea; Amon, Sven; Meier, Trixi; Schmand, Ralf; Hanenkamp, Nico (Applied Mechanics and Materials, 2018)
This paper aims to expand the use of CO2 blasting by investigating a cryogenic deburring method for machined metallic materials. In advance to the actual deburring experiments, a streaming analysis based on high-speed video records was conducted for different blasting technologies, in order to gain deeper knowledge about their underlying active principles. For the titanium alloy Ti-6Al-4V and the stainless steel X6CrNiMoTi17-12-2, deburring experiments with three different blasting techniques were conducted and evaluated. It has been shown that cryogenic deburring has the potential to represent an alternative deburring solution for metals.
Keywords: cryogenic deburring; deburring with CO2; CO2-based blasting technologies; CO2 snow blasting; dry ice blasting

Investigation of the influence of lubricating oils on the turning of metallic materials with cryogenic minimum quantity lubrication - Gross, Daniel; Bigelmaier, Matthias; Meier, Trixi; Amon, Sven; Ostrowicki, Nicolai; Hanenkamp, Nico (Procedia CIRP, 2019)
Nowadays, cooling and lubrication for cutting processes in industry are mostly based on flood cooling. The enormous quantities of lubricants are not only harmful for the environment and employees, but also require additional infrastructure and pre-treatment, while processed parts require an additional cleaning step due to metallic swarf which leads to high manufacturing costs. The cryogenic minimum quantity lubrication could serve as an alternative cooling and lubrication concept, which might be suitable for high-alloyed steels and titanium alloys as well. Within this work the potential of this new concept of cooling and lubrication was investigated by the utilization of different lubricants for turning of Ti6Al4V, X5CrNi18-10 and 42CrMo4 workpieces with a main focus on cutting forces, tool wear and resulting surface roughness. Required data indicates that the cryogenic minimum quantity lubrication might indeed be suitable to replace the conventional wet processing routes. The proper lubricants are selected to match the material to be machined.<br
Keywords: Turning; Cryogenic Machining; Minimum Quantity Lubrication; Ti6Al4V; 42CrMo4; X5CrNi18-10

Technologieentwicklung kryogener Entgratungsstrategien für metallische Werkstoffe - Amon, Sven; Hanenkamp, Nico (2022)
Keywords: Kryogene Entgratung; Kryogene Entstützung; Trockeneisstrahlen

Theoretical Investigation of the Influence of Different Chamber Geometries on the Agglomeration Capacity of Carbon Dioxide - Gross, Daniel; Ferguson, Nikolas; Amon, Sven; Hanenkamp, Nico (Applied Mechanics and Materials, 2017)
This paper addresses the complicated process of carbon dioxide particle formation (agglomeration), which is essential for carbon dioxide snow blasting. Most effective process methods in this field possess a dedicated location where agglomeration is likely to occur. Research has shown that successful agglomeration is a key factor when cleaning or deburring with solid carbon dioxide. The following describes the mechanisms of carbon dioxide (CO2) snow agglomeration inside this so-called agglomeration chamber. The elements of larger size, as well as an irregular shape directly lead to the increase of effectiveness. Therefore, it is necessary to determine how to improve this process for the purpose of dealing with difficult workpieces and materials and broaden the possibilities of carbon dioxide blasting. One of the main factors of agglomeration is turbulence. In short, the more turbulent activity that takes place, the better is the particle formation of solid carbon dioxide. Numerous geometries were created with different inserts, such as static mixers or angled tubes, in hope to increase turbulence. The basic idea is to implement these geometries in computational fluid dynamics (CFD) and finally proceed to an evaluation and comparison of the simulation results, in order to select the best candidates for optimization and realization.
Keywords: Agglomeration; Carbon Dioxide; Computational Fluid Dynamics (CFD)